Answer:
[tex]x^{2} - 3x - 10[/tex]
Step-by-step explanation:
To start, lets form our polynomial factors from our zeroes.
x = -2
x + 2 = 0
x = 5
x - 5 = 0
Now lets put these into factored form by moving them into parenthesis and multiplying them with each other!
(x+2)(x-5)
We can start moving them out! I am going to use FOIL, but you could also use distributive or any other method/property.
x · x = x²
x · -5 = -5x
x · 2 = 2x
2 · 5 = 10
Now lets put our terms into our polynomial function, based on the order of the powers.
[tex]x^{2} - 3x - 10[/tex]
We are done! Hope this helps!